2018
DOI: 10.24953/turkjped.2018.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Does microbial resistance profile change in community-based intra-abdominal infections? Evaluation of the culture results of patients with appendicitis

Abstract: Does microbial resistance profile change in community-based intra-abdominal infections? Evaluation of the culture results of patients with appendicitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 16 publications
1
1
0
1
Order By: Relevance
“…Although underpowered, the results of this study showed that both hospital sites should focus on developing and testing targeted, interdisciplinary prevention efforts for E coli because this organism was found in almost half of the SSI cases (n = 9, 45%). This result is consistent with other studies on SSIs following abdominal surgery, showing E coli alone and in combination with other organisms such as Enterococcus species, Staphylococci , and Klebsiella 13,20,21 . Collaboration among health care workers is needed to discuss current protocols and to determine whether a single intervention (eg, alcohol‐based skin preparation, glycemic control for all patients during surgery, warming device to maintain perioperative normothermia, using an antimicrobial prophylaxis protocol to achieve bactericidal concentrations in serum and tissues during surgery) or a bundled approach would be most effective 16,17 .…”
Section: Discussionsupporting
confidence: 85%
“…Although underpowered, the results of this study showed that both hospital sites should focus on developing and testing targeted, interdisciplinary prevention efforts for E coli because this organism was found in almost half of the SSI cases (n = 9, 45%). This result is consistent with other studies on SSIs following abdominal surgery, showing E coli alone and in combination with other organisms such as Enterococcus species, Staphylococci , and Klebsiella 13,20,21 . Collaboration among health care workers is needed to discuss current protocols and to determine whether a single intervention (eg, alcohol‐based skin preparation, glycemic control for all patients during surgery, warming device to maintain perioperative normothermia, using an antimicrobial prophylaxis protocol to achieve bactericidal concentrations in serum and tissues during surgery) or a bundled approach would be most effective 16,17 .…”
Section: Discussionsupporting
confidence: 85%
“…To accomplish this discrimination, we searched MEDLINE via PubMed on Juli 15 th , 2022 for the name of the bacteria AND “human” AND “infection”. For rarely published bacteria, we set an arbitrary threshold at any bacteria with less than 0.3% of publications on human infections with E. coli , the most common bacteria in human appendicitis ( Wilms et al., 2011 ; Fallon et al., 2013 ; Kenig and Richter, 2013 ; Bhangu et al., 2015 ; Tartar et al., 2018 ; Son et al., 2020 ; Plattner et al., 2021 ).…”
Section: Methodsmentioning
confidence: 99%
“…En nuestro estudio la mayoría de los niños con apendicitis presentan infección por E. coli (80.14%) 28,[33][34][35][36][37] . También encontramos que la prevalencia de P aeruginosa es del 7.45%, en la literatura se ha demostrado una prevalencia del 5.3% al 23% 35,[37][38][39] .…”
Section: Discussionunclassified